Acquisition, processing and enhancement of multi-channel radiometric data collected with ultralight aircraft mounted detectors - Coetzee, Hendrik (My University, 2008)
An ultralight aircraft based airborne geophysical system was developed and operated by the Council for Geoscience during the period 1997-2004. The aim of this project was to collect geophysical data at lower cost and higher resolution than was possible using conventional airborne systems. This dissertation describes the development of the radiometric systems used in the ultralight airborne survey project. During the course of the study, a number of obstacles to the successful collection and processing of radiometric data with the ultralight-mounted systems were encountered. These are described and solutions proposed. To facilitate the development hardware systems and processing methods, a Monte Carlo simulation method was developed to produce spectra containing realistic signal and noise components. This method was applied to the selection of detector materials and the specification of detector sizes as well as being used to simulate large spectral data sets for the development and testing of processing and calibration procedures. Radiometric data follow a Poisson Distribution, with the signal to noise ratio being dependent on the count rate recorded, which, in turn, depends on the size of the detector used. The ultralight aircraft were capable of carrying a detector one eighth the size of that used in conventional systems. To allow for the use of the smaller detector, the noise adjusted singular value decomposition (NASVD) processing technique was employed. While this technique is commonly applied in noise-reduction, the original application, namely the determination and mapping of spectral components was also utilised. iii During the course of the study no suitable calibration facilities were available inside South Africa. This necessitated the development of a spectral stripping method, utilising a technique generally applied to much higher resolution spectral data collected under laboratory conditions. Simulation studies and practical application showed that this method performs well, in some cases outperforming the conventional stripping method. The method is also applicable to the study of anthropogenic radionuclides, where suitable calibration facilities are generally unavailable. An alternative to the conventional method of altitude correction was also applied to the radiometric data collected with the ultralight-mounted systems. Using simulated data, a spectrometer based on a bismuth germanate (BGO) detector was designed and constructed. This material is significantly denser than the more usual thallium activated sodium iodide used for detector fabrication and has a higher effective atomic number, giving it a greater photopeak efficiency. However the poor light production of this scintillation material results in a poorer energy resolution than a conventional detector. Initial tests using small BGO detectors were promising and a larger detector was acquired and tested. Unfortunately the poor energy resolution and high cost of BGO detectors led to the conclusion that they did not offer the advantages initially hoped for. Nevertheless a number of successful surveys were flown using the BGO detector. Ultralight-mounted systems were found to be ideal for small surveys where high spatial resolution is required. The ultralight systems were successfully applied to the detection of radioactive pollution on a number of sites in the Witwatersrand and related gold fields and one site where anthropogenic radionuclide contamination was present. In some cases, the data could be compared to data collected using a conventional airborne radiometric system. Here the ultralight- mounted systems were found to perform satisfactorily, albeit with a poorer signal to noise ratio except where adverse flying conditions necessitated flying at high altitude. The strengths, weaknesses and potential applications of ultralight-mounted airborne radiometric systems are discussed.
Keywords: airborne radiometric systems; ultralight aircraft